1972
DOI: 10.1097/00006534-197202000-00053
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland tumors in the parotid gland, submandibular gland and the palate region

Abstract: The relative incidence of the different types of salivary gland tumors and their prognoses has been shown to vary with the location in a study of 2,867 patients with tumors in the parotid gland, submandibular gland, and the palate region. After histologic reexamination and reclassification, 2,513 of the 2,867 tumors were classified as salivary gland tumors. The incidence of salivary gland tumors was strikingly high in the parotid gland, i.e., about twelve times more common in the parotid gland than in the subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
70
1
15

Year Published

1991
1991
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 0 publications
7
70
1
15
Order By: Relevance
“…Salivary gland tumours are rare tumours of the head and neck region (Eneroth, 1971;Eveson and Cawson, 1985). The diagnosis and treatment of these tumours represent a challenge for head and neck surgeons for several reasons: they occur relatively infrequently, are found in diverse sites and show a great deal of variation in histological characteristics, clinical appearance, pathogenesis and 5-year (5Y) survival probability (Spiro and Dubner, 1990).…”
mentioning
confidence: 99%
“…Salivary gland tumours are rare tumours of the head and neck region (Eneroth, 1971;Eveson and Cawson, 1985). The diagnosis and treatment of these tumours represent a challenge for head and neck surgeons for several reasons: they occur relatively infrequently, are found in diverse sites and show a great deal of variation in histological characteristics, clinical appearance, pathogenesis and 5-year (5Y) survival probability (Spiro and Dubner, 1990).…”
mentioning
confidence: 99%
“…Majority of them are benign tumors and occurs mostly in the major salivary glands with the parotid gland being the most affected gland while the submandibular and sublingual glands are less affected (Rai et al, 2011;Patil et al, 2014). Eneroth (1971) reported that 80% of pleomorphic adenoma of the parotid gland, are found within the superficial lobe. Within the mouth, the palate constitutes the commonest site (60%) of the minor salivary glands tumors while other sites less affected are the lips, tongue and buccal mucosa, also about 80 to 90% of benign salivary gland tumors are pleomorphic adenoma (Rai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Tükürük bezinden kaynaklanan tümörler erkek ve kadınlarda eşit olarak görülür ve 20-60 yaşları arası dönem en sık görüldüğü dönemdir (1) . Bu tümörlerin %75-80'i parotis bezi kaynaklıdır (2) . Parotis bezi tümörlerinin %80'i benign olup, bunların %75'i pleomorfik adenom, %15-20'si Warthin tümör, %10'u da diğer benign tükürük bezi tümörlerinden meydana gelmektedir (3,4) .…”
Section: Introductionunclassified